Dinâmica populacional, comportamento reprodutivo e uso do habitat em Telebasis carmesina Calvert, 1909 (Odonata: Coenagrionidae) no Cerrado de Uberlândia - MG - Martins, Fernanda Alves (2010)
The Neotropical damselfly Telebasis carmesina (Odonata: Coenagrionidae) is a common species in the Cerrado, a Brazilian savanna and even though, nothing is known about its natural history and ecology. This study aimed to investigate the population ecology, the habitat use and the breeding behavior of this species. It was conducted at a pond in the Natural Particular Reserve at Clube de Caça e Pesca Itororó de Uberlândia, between July/2008 and October /2009. The data was collected through the markrecapture method, using an insect net and a metal precision caliper. In addition, 81 hours of behavioral observations was taken. An amount of 1133 individuals were captured. December and November/2008 comprised the highest number of marked males, while September and October/2008 presented the higher abundance of females. The abundance of individuals was directly related to the air temperature and relative air humidity and it affects the individuals size, that is, the bigger the males abundance, the smaller was the total length of them, which generally are smaller than females. The males size also varied between the seasons of the year, except in summer and auntumn, and the females had different average of sizes between spring and summer months. The males longevity varied between the seasons and during the breeding season October to April was 7,099 (±0,719; X±SE) days. In this study, both males and females had concentrated mainly in the pond and used the macrophytes Eliocharis sp. and Pontederia parviflora as main perching surface, mating and oviposition. The polygynous mating system through scramble competition was evidenced during observations and supported by the smaller size of males and the absence of territory guarding behavior. The breeding behavior was frequently observed during the midmorning. T. carmesina s mate involved sperm transfer to edeagous, tandem and wheel positions and some evidences suggest that there is males sperm displacement in the species. The oviposition occurs together with the male, in tandem. Sex ratio varied throughout the months, with the closest value in relation to 1:1 ratio in September (1:3,48) and the most distinct value in January (1:27,4). Males exhibited three types of aggressive displays, similarly to other studies in literature: i) chase, when a male run after other male, going back to its original position or its position is displaced by the other male; ii) threat display or wing spread, when a male, realizing the approach of another male, spreads his wings, and iii) attack, which can occurs through the use of the legs, abdominal appendages or mouth parts. The agonistic behavior is directed toward to conspecific males; however aggressive interactions can also occur between heterospecific individuals. Telebasis carmesina presents important features related to sexual selection, such as sexual size dimorphism and sex ratio male biased. Moreover, the habitat use by males and females are spatially and temporarily different.